RETHINKING COMMUNITY FORESTRY PROGRAM: CURRENT SITUATION AND FUTURE ISSUES IN GUNUNGKIDUL, INDONESIA - , AGUNG WIDIATMOKO, Ir. Suryanto, MSP. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Community forestry has been promoted as a good program for solving the problems of deforestation and rural poverty. This program has been implemented for more than 10 years in Indonesia, but it has not yet shown satisfactory results. This study aims to explore characteristics of community forestry, clarify benefits for local peoples from community forestry, and make an assessment of the current situation. To achieve the objective of the study, we purposely chose 129 respondents in Gunungkidul Regency and analyzed socioeconomic factors, demographic factors, the activities of respondents, and the benefits from community forestry. The results show that members of community forestry programs can be characterized by a low level of education, with the majority being farmers and having a low income. Members cannot gain more benefits from forestland now in spite of playing an active role in community forestry. They cannot do intercropping anymore and cannot harvest timber. The problems of community forestry in Gunungkidul Regency are the small benefits from forestland and low levels of knowledge of timber-harvesting methods. Giving education and training to members is needed